"You look very well for a transplant" : autoethnographic narrative and identity in chronic kidney disease, kidney failure and the life post-transplant - Richards, Roselee Jayne (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2012.